Understanding the Background of Personality Disorders and the Influence of Early Experiences with Parents to their View of God - Lanny Pranata (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2023)
Early relationship is very significant in developing a healthy personality. What a child experience during first three years of life can have a lifelong impact. Early relationships not only act as a template of the brain, but also mold and shape the child’s ability for future relationships with others. Early relationship also becomes the determinant of normal or pathological splitting. Splitting is universal and not all splitting cause a pathology. Maternal-availability is essential during first three years of life. Normal splitting can happen when good-enough mother on some occasion is unavailable or unable to attend to the infant and meet his needs. The child can tolerate the good-enough mother’s unavailability at certain times because he or she is in ‘holding environment’ that makes the child feel secure, protected, and not excessively frustrated. Pathological splitting can happen when the infant receives excessively unsatisfying, frustrating and abusive experience. Severe splitting makes one to see everything in terms of black and white. He or she is not able to accept bad and good at the same time or cannot accept paradoxical qualities in others. A normal person can accept this paradoxical quality, but a personality disorder person cannot accept this paradoxical quality. Finally, early relationships influence one’s relationship to God, how he or she sees God and experience God. Three studies have found that early relationship with parents, whether secure or insecure relationships can influence how one sees God and relates to God (Gravitt, 2011; Pehr Granqvist, 2007; Rosalinda Cassibba, 2013). One who has a secure attachment with his or her parent, tend to trust God and has a secure relationship with God as well. As a therapist, it is essential that we provide a secure base for our patients or clients. Psychodynamic therapy is the kind of therapy that proved to help patients with Personality Disorders. Successful treatment should not only relieve symptoms but also make intrapsychic change by providing patients with a relationship that enables them to resolve the splitting of their ego.